(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This article analyzes the economic consequences of the state budget deficit and public debt. The state budget deficit is considered as the difference between government expenditures and revenues. The aim is to analyze the causes of this deficit, its impact on the economy, and the problems associated with the growth of public debt. This article shows the main trends through statistical data and graphs.